Twenty-first century fictions of terrorism - Keeble, Arin, 1977- (Edinburgh University Press, 2024)
"A comprehensive study of how fiction has depicted and responded to terrorism in the twenty-first century. Examining novels by celebrated authors, some neglected and some brand new texts, Arin Keeble offers a detailed analysis of the ways novels from around the world have represented terrorism in the early twenty-first century. Over five chapters, he uncovers a movement away from event-based narratives toward depictions of terrorism as a violent symptom or feature of twenty-first century world-systems and neoliberalism. Beginning with the early literary response to 9/11 and the 9/11 novel genre, the book moves through more recent depictions of the endless 'war on terror', state terror, white nationalist terror and historical narratives of terror that resonate in the current political climate. In doing so, it examines the changing ways literature has sought to make sense of both the reasons why terrorism occurs and the effects it has on victims, survivors and international and intercultural relations"--